Comprehensive performance evaluation of sliding-bearing wind turbine gearboxes - Li, Yao (Strojniški vestnik, 2025)
Considering the structural characteristics and multi-source excitations of sliding-bearing wind turbine gearboxes, this study constructs a multi-body dynamic model of high-power sliding-bearing wind turbine gearboxes. A comprehensive performance evaluation methodology is proposed, integrating the analytic network process (ANP) with an improved fuzzy comprehensive evaluation (IFCE). A multidimensional comprehensive performance evaluation framework, emphasizing the practicality and cost-effectiveness is developed consisting of target, criterion, and indicator layers. The key evaluation indicators identified within this framework include the main shaft bearing support force, transmission system reliability, load-sharing coefficient, vibration characteristics, and power density. Utilizing ANP and IFCE methodologies the comprehensive performance of two sliding-bearing wind turbine gearboxes is systematically assessed.
Keywords: analitični mrežni proces (ANP); analytic network process; celovita ocena zmogljivosti; comprehensive performance evaluation; fuzzy comprehensive evaluation; mehka celovita ocena (FCE); multidimensional evaluation indicators; sliding-bearing wind turbine gearbox; večrazsežni kazalniki ocenjevanja; zobniški prenos vetrne turbine z drsnimi ležaji